The Establishment of Independence and Creativity Value of Early Childhood at TPA Taman Belia Candi Semarang - Widiasih, Embun Melati; Sutarto, Joko; Suminar, Tri (Universitas Negeri Semarang, 2017)
The problems of the research are (1) how the establishment of independence value of early childhood in TPA (one Daycare) of PAUD Taman Belia Candi Semarang city, (2) how the establishment of creativity value of early childhood in TPA (one Daycare) of PAUD Taman Belia Candi Semarang city. This research aimed to describe the establishment of independence value of early childhood in TPA (One Daycare) of PAUD Taman Belia Candi Semarang city and describe the establishment of creativity value of early childhood in TPA (One Daycare) of PAUD Taman Belia Candi Semarang city. This study used qualitative descriptive approach with the research subject from this study were learners, educator, nursemaid, Daycare coordinator, and headmaster also learners’ parents. The collecting data technique obtained from observation, interview, and documentation. This research result, the establishment of independence value done through custom establishment, role model, supporting area and then adjusted with the children development level and the establishment of creatvity value done through play learning activity. suggestions in the establishment of independence and creativity value include the quality improvement of APE tool and infrastructure and pay attention to the level of children development by cooperate with parents, school, and surroundings.